Necrotizing acute pancreatitis with gastric wall necrosis and biliopancreatic fistula: a case report - Duque, Mariana S.; Lemos, Mariana C.; Almeida, Nuno P.; Bernardes, António S.; Tralhão, José G. (International Surgery Journal, 2025)
Chronic pancreatitis (CP) is a condition characterized by chronic inflammation of the pancreatic gland. This multifactorial condition might be associated with different clinical manifestations but patients may also experience acute exacerbations. In rare cases, these acute episodes can lead to serious, life-threatening complications requiring surgery. Gastric wall necrosis is a rare complication of severe acute pancreatitis (AP) requiring a rapid specialized approach. Biliopancreatic fistula can also arise in this context, particularly in acute necrotizing pancreatitis. Both biliopancreatic fistula and gastric necrosis can determine serious management challenges, particularly regarding the surgical approach. We present the case of a male patient in his late fifties with history of alcohol-related CP. This patient experienced a new episode of acute necrotizing pancreatitis after several years of being clinically stable and asymptomatic. Initial management was performed in another centre. This included damage control surgery, due to gastric wall necrosis, with gastric partial resection without anastomosis and the patient was subsequently transferred to our center to continue treatment and restoration of esophagogastric continuity. In the second and final surgical approach, 10 weeks after the index surgery, esophagogastric anastomosis was performed and a biliopancreatic fistula was intra-operatively identified and managed with endoscopic retrograde cholangiopancreatography (ERCP) through the gastric stump with placement of a plastic biliary stent bypassing the fistula. Association of acute gastric wall necrosis and biliopancreatic fistula is a rare and challenging complication of AP. Although definitive treatment may need to be delayed to a secondary surgery, this case highlights the potential for successful management in specialized centres with an experienced biliopancreatic team.